Perancangan Sistem Informasi Akuntansi penggajian dengan mengunakan Microsoft Visual Basic 2008 dan database MySQL - Dwi Puspa Lestari (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2017)
KSP.Kopdit Borromeo is a company engaged in the service. In KSP. Kopdit Borromeo who is responsible for the performance of employees in a company which is part of the manager. The author conducted research on the treasurer in charge of payroll employees. But the company still uses KSP.Kopdit Borromeus payroll manually, ie by using Microsoft Excel. To reduce the existing problems, the authors take the title "Payroll Accounting Information System Design in KSP.Kopdit Borromeus by using Microsoft Visual Basic 2008 and MYSQL. The research design is the design of the study authors use primary data and secondary data. The method used is descriptive research methods, survey. This type of research is academic research. The type of data used is qualitative and quantitative. Data collection techniques used were interviews. System development method used is output-oriented methodologies, processes and data. The structure of the development of the system used is the waterfall. The design of the information system used context diagrams, data flow diagrams, and flowcharts. The author makes the design of the payroll accounting information systems, to assist the transaction processing and financial reporting to the KSP. Borromeus well be computerized.